2014
DOI: 10.3855/jidc.4276
|View full text |Cite
|
Sign up to set email alerts
|

Effective surveillance of vector dynamics of Aedes aegypti in a hospital setting in Cuiabá, Mato Grosso, Brazil

Abstract: The results indicate that this hospital may be considered an environment for the spread of dengue and hence strategic actions, including control measures and programs aimed at preventing the transmission of this vector, must be implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Eight studies examined arbovirus vector distribution and ecological suitability in the Americas. Five were conducted in the United States [93,9598], two in Brazil [99,100], and one in Peru [101]. Johnson et al [97] created a predictive model of population dynamics in the United States based on vector presence data, Little et al [93] found that Ae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies examined arbovirus vector distribution and ecological suitability in the Americas. Five were conducted in the United States [93,9598], two in Brazil [99,100], and one in Peru [101]. Johnson et al [97] created a predictive model of population dynamics in the United States based on vector presence data, Little et al [93] found that Ae.…”
Section: Resultsmentioning
confidence: 99%
“…albopictus was present in 59% of analyzed Brazilian municipalities. Across these studies, we can conclude that mosquitoes are often highly clustered in their distribution [99,101] and that distributional determinants may differ between Ae. aegypti and Ae.…”
Section: Resultsmentioning
confidence: 99%